An Empirical Study on Quality of Life Among Chinese University Students: Application of the KIDSCREEN-52 Instrument - Lin, Peiyu; Saenubol, Kanchit; Srisawat, Patcharaporn (Journal of Ecohumanism, 2025)
This study aims to assess the quality of life (QoL) of Chinese university students using the KIDSCREEN-52 questionnaire and to explore its applicability in the context of higher education in China. Through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), seven key dimensions of QoL were identified: emotional well-being and self-perception, family and peer relationships, psychological health, school environment, physical health, autonomy, and financial resources. Although the standardized regression weights showed strong associations between individual items and their respective dimensions, the overall model fit indicated that the direct application of the KIDSCREEN-52 in China requires further adjustment. Certain items need to be reclassified or removed to better align with the cultural and contextual realities of Chinese university students. The findings emphasize the importance of social support, school environment, and psychological health in shaping overall QoL, while also highlighting challenges in emotional well-being, self-perception, and financial stability. This research provides theoretical and practical insights for localizing the KIDSCREEN-52 questionnaire and designing targeted interventions to enhance the QoL and well-being of Chinese university students.